IMPLEMENTASI MESIN PENEBAR DAN PERATA YANG ERGONOMIS UNTUK MENINGKATKAN KESEHATAN KERJA DAN PRODUKTIVITAS UKM TEPUNG UMBI - Siti Aqilla Sayyidha Winata Praja; Intan Berlianty; Apriani Soepardi; Laila Nafisah; Puryani Puryani; Mochamad Chaeron (MAJU : Indonesian Journal of Community Empowerment, 2026)
Small and medium enterprises in flour processing still rely heavily on manual drying processes, which pose high risks of musculoskeletal disorders and low productivity. This community service program aimed to implement an ergonomically designed spreading and leveling machine to improve working posture and production performance at Kusuka Ubiku SME in Bantul Regency. The program was conducted through problem identification, assessment of workers’ physical complaints using the Nordic Body Map, posture risk analysis using Rapid Entire Body Assessment, ergonomic machine design based on anthropometric data through the Need–Idea–Decision–Action approach, followed by on-site implementation and mentoring. The results show a significant reduction in posture risk from a high-risk category to a low-risk category and an increase in worker productivity by 53.6 percent. These findings demonstrate that the application of ergonomics-based appropriate technology effectively enhances occupational health and operational efficiency in food-processing SMEs.